Robert Jordan's The wheel of time : the eye of the world. Volume one - Dixon, Chuck, 1954- (Dynamite Entertainment, 2011)
Rand al'Thor and his friends are looking forward to the Bel Tine festival when a peddler arrives to tell that someone claiming to be the Dragon Reborn and to wield the One Power is being ridden against by the Aes Sedai of Tar Valon. Dark strangers, warriors, and an attack by monstrous Trollocssignal the end of Rand's peaceful childhood and the beginning of his life.